Profiling news consumption on social media - Veronika, Veronika; Raharjo, Agustinus Eko (Jurnal Komunikasi Profesional, 2021)
Social media is an exciting platform to be researched at this time because users are increasing. This condition is a challenge for the media to be able to take advantage of this phenomenon into a great opportunity. The concept of social media journalism is growing as many media use social media with diverse objectives. A lot of studies have tried to see from a variety of spectacles. This research fills the research void related to the consumption of news through social media in Indonesia based on uses and gratification theory and social media concept. The survey conducted by distributing questionnaires online for two months to get 736 respondents from various regions in Indonesia. The result is that social media is not the main place for Indonesian people to look for news. Most of the respondent is still looking for news through two mediums, namely offline and other online. People who access news through social media are satisfied, but they do not have confidence in the news on social media. Besides understanding news consumption patterns on social media, this research suggests a model that the media needs to understand to utilize social media more effectively.